Service with - a smile if possible - Abd Razak, Dzulkifli (2007)
THE government wants the public delivery system to be drastically improved. Chief Secretary to the government Tan Sri Mohd Sidek Hassan has ordered heads of department to make unannounced visits to public counters to check out the situation. The chief secretary believes the most important part of service is speed. "Everyone expects to be served fast, be it at the government departments, banks or restaurants. I would rather be served fast with or without a smile rather than not be served at all. But the best and ideal service is one that is fast and with a smile," he said. This is possible going by the examples he singled out—Subang Jaya's Municipal Council, the Employees Provident Fund office in Petaling Jaya and Immigration Department offices.